Uwarunkowania i potrzeba integracji przedsiębiorstw sektora rolno-żywnościowego w warunkach dominacji korporacji globalnych - Woźniak, Leszek; Ziółkowski, Bożydar; Dziedzic, Sylwia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of this paper was to present a need for integration process in sector of agri-food enterprises. The main reason to make this is dominating position of global corporations. The emerging conclusions suggest that it is necessary to include into the process of integration the principle of sustainable development. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 377-382